Enhancement of Corrosion Resistance and Discharge Performance of Mg–5Li–3Al–1Zn Sheet for Mg-air Battery via Rolling. Issue 11 (15th July 2020) - Yang, Huabao; Wu, Liang; Jiang, Bin; Lei, Bin; Liu, Wenjun; Song, Jiangfeng; Atrens, Andrej; Huang, Guangsheng; Zhang, Dingfei; Pan, Fusheng
Abstract : The corrosion behavior at open circuit potential (OCP) and the discharge performance under impressed anodic current of Mg–5Li–3Al–1Zn (LAZ531) alloy sheets with different rolling reductions are investigated using hydrogen evolution, potentiodynamic polarization, electrochemical impedance spectroscopy, and galvanostatic discharge measurements. The results show that rolling increases the corrosion resistance and strengthens the discharge ability of LAZ531 alloy, which is attributed to the increased density of twins and the change of grain orientation. Of those, the LAZ531 alloy with 20% rolling reduction (LAZ531%-20%) has high and steady discharge voltage at small current density for long time, with the values of 1.490 V at 2.5 mA cm −2 and 1.411 V at 10 mA cm −2 . The grain boundaries and twins play the same roles on the corrosion and discharge processes, which are attacked preferentially than the grain interiors and accelerate the dissolution of LAZ531 alloy.